The Lisbon strategy and the EU's structural productivity problem - Roger, Werner; Denis, Cecile; McMorrow, Kieran; Veugelers, R.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2005)
The structural nature of the EU's productivity downturn is confirmed by the analysis in this paper, with the bulk of the deterioration emanating from an outdated and inflexible industrial structure which has been slow to adapt to the intensifying pressures of globalisation and rapid technological change. The EU's productivity problems are driven by the combined effect of • an excessive focus on low and medium-technology industries (with declining productivity growth rates and a globalisation-induced contraction in investment levels); • an inability to seriously challenge the US's dominance in large areas of the ICT industry, as reflected in the relatively small size of its ICT production sector; and finally, • its apparent slowness in reaping the productivity enhancing benefits of ICT in a range of ICT-using industries, although measurement issues severely complicate an assessment of the gains from ICT production and diffusion.
Economic Papers